The effect of plant active substances on cognitive function in healthy older adults: a systematic review and network meta-analysis of randomized controlled trials - Feng, Xueyan; Fan, Shuangbo; Wei, Fengqin (Frontiers in Pharmacology, 2026)
BackgroundWith the accelerating global population aging, age-related cognitive decline has become a significant health concern for the older adults. The limited efficacy and common side effects of pharmacological interventions have made the exploration of safe non-pharmacological strategies an urgent need. Plant active substances have drawn much attention due to their multi-target neuroprotective properties, there is a lack of systematic comparative research on cognitive function in healthy older adults.ObjectiveTo assess the effects of plant active substances on various domains of cognitive function in healthy older adults through a network meta-analysis (NMA).MethodsComprehensive searches were conducted in Embase, PubMed, Cochrane Library, and Web of Science (up to 31 December 2024). Primary outcomes included learning and memory, complex attention, executive function, language, and perceptual-motor skills. NMA was performed using Stata 15.1, with cumulative ranking curve area (SUCRA) for intervention ranking; consistency and publication bias were examined.ResultsAfter screening, 25 eligible studies with 1861 healthy older adults, evaluating 10 plant active substances, were included. Specifically, 23 studies included learning and memory functions, 18 studies included complex attention, 16 studies included executive functions, 4 studies included language functions, and 3 studies included perceptual-motor functions. The research results showed that based on the SUCRA values, raisins (95.1%) and tart cherry (89.5%) were the most likely to be the best intervention for improving learning and memory functions. The bacopa monnieri compound (91.3%), curcumin (89.3%), and tart cherry (88.9%) ranked in the top three in the executive function domain. Bacopa monnieri compound (93%) and raisin (80.7%) ranked in the language function category. Guarana (90.3%) had the highest probability in the perceptual-motor domain. The intervention effects on complex attention functions were generally limited.ConclusionThe NMA results indicate that in terms of learning and memory functions, raisin and tart cherry ranked higher; in terms of executive functions, the bacopa monnieri compound demonstrated a relatively better intervention effect, providing an important basis for non-drug interventions for cognitive health in the healthy older adults. Future research should focus on long-term safety, dosage optimization, and synergistic mechanisms to promote functional food development.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CDR420251032046.